Climatic treelines: conventions, global patterns, causes - Körner, Christian (ERDKUNDE, 2007)
The high altitude treeline phenomenon is discussed with a global perspective. If one disregards local/regional (including anthropogenic) reasons for the absence of trees, the high elevation treeline is found at surprisingly uniform growing season temperatures worldwide, while other types of thresholds (including the warmest month temperature) do not work on a global scale. This phenomenon is explained by the close aerodynamic coupling between tree crowns and atmospheric conditions. It is shown that the treeline position can be predicted well by thermal thresholds alone, which makes it an ideal biogeographic reference line in modelling, for instance to estimate the global mountain forest area.